Use of trusts as a vehicle for estate (tax) planning in South Africa - Moosa, Fareed (Department of Private Law, 2021)
Estate planning has been described as the process whereby a person acquires property, ensuring that he derives maximum benefits from his ownership and the enjoyment thereof during his lifetime, and that as much as possible and in the most economical manner with the minimum erosion thereof shall devolve upon his heirs when he dies. ( 1) The objective of estate planning is thus, in essence, the disposal of property during the estate owner's ('the planner') lifetime or upon his death.